Questions of legal content and meaning of civil (Journal of actual problems of jurisprudence, 2019)
This article focuses on the scientific study of the legal content and value of one of the most important civilinstitutes – civil liability. Also were discussed the ways and measures of civil rights protection.Keywords: Civil liability, legal content and value of civil liability.